2017
DOI: 10.1093/nar/gkx1019
|View full text |Cite
|
Sign up to set email alerts
|

The OMA orthology database in 2018: retrieving evolutionary relationships among all domains of life through richer web and programmatic interfaces

Abstract: The Orthologous Matrix (OMA) is a leading resource to relate genes across many species from all of life. In this update paper, we review the recent algorithmic improvements in the OMA pipeline, describe increases in species coverage (particularly in plants and early-branching eukaryotes) and introduce several new features in the OMA web browser. Notable improvements include: (i) a scalable, interactive viewer for hierarchical orthologous groups; (ii) protein domain annotations and domain-based links between or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
227
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 221 publications
(229 citation statements)
references
References 41 publications
(50 reference statements)
1
227
0
Order By: Relevance
“…The UPR in fission yeast operates through selective decay of mRNAs encoding proteins destined for the secretory pathway [18,19]. We note that although the C10:0-containing molecules constitute less than 20% total phospholipids ( tend to be shorter than those residing in the later compartments of the secretory pathway [22]. Curiously, most single-pass TM proteins that exhibit shortened TMDs in S. japonicus as compared to other fission yeasts are predicted to function largely at the ER, ER-organelle contacts and cis-Golgi (Supplemental Table 10).…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…The UPR in fission yeast operates through selective decay of mRNAs encoding proteins destined for the secretory pathway [18,19]. We note that although the C10:0-containing molecules constitute less than 20% total phospholipids ( tend to be shorter than those residing in the later compartments of the secretory pathway [22]. Curiously, most single-pass TM proteins that exhibit shortened TMDs in S. japonicus as compared to other fission yeasts are predicted to function largely at the ER, ER-organelle contacts and cis-Golgi (Supplemental Table 10).…”
Section: Resultsmentioning
confidence: 85%
“…3F). Furthermore, the fas s. j. Membrane composition and physical properties may impose constraints on the structure of transmembrane parts of integral membrane proteins [22]. The comparisons of predicted transmembrane helices (TMHs) in all orthologous groups of transmembrane proteins between S. pombe and other fission yeast species (1:1:1:1 orthologs) showed that predicted S. japonicus TMHs contained many small non-polar amino acids and fewer large non-polar residues compared to the rest of fission yeasts (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our sampling included species from mammals, birds, reptiles, amphibians, coelacanths, holostean fish, teleost fish, chondrichthyans and cyclostomes (Supplementary File 1). Protein sequences were obtained from the Orthologous MAtrix project (OMA) (Altenhoff et al, 2018). In cases where the species were not included in the OMA project, we searched the NCBI database (refseq_genomes, htgs, and wgs) using tblastn (Altschul et al, 1990) with default settings.…”
Section: Sequence Data and Phylogenetic Analysesmentioning
confidence: 99%
“…This naive approach finds all similar pairs, but it scales poorly as the number of proteins grows. Several databases of similar proteins produced by this approach exist, including OMA [2] and OrthoDB [26]. Analyzing their contents is costly.…”
Section: Introductionmentioning
confidence: 99%